Physicochemical and pollen analysis of Local honeys from the Lima Valley (Portugal) - Estevinho, Leticia M. (2014)
An evaluation was done on the physicochemical quality of nineteen (n=19) Apis mellifera honeys produced in the Lima Valley, Portugal. The rural landscape of the Lima Valley is valuable in social, environmental and economic terms and its conservation and preservation are essential. The evaluated physicochemical characteristics were: moisture, ash, electrical conductivity, pH, hydroxymethylfurfural (HMF), free acidity, apparent sucrose, reducing sugars and diastase activity. All honey samples met the International physicochemical quality standards. A short study of pollen source was done by acetolisis method. The families Fabaceae and Rosaceae were found with 6 and 2 pollen types each respectively. The most important pollen source is Erica, moreover two samples are listed as Erica monofloral honey.